Decision making in developing countries regarding participation in regional economic organizations : comparison of Andean Pact, ECOWAS and ASEAN case - Brown, Leann Myra (Michigan : UMI, 1988)
Theses (Ph.D)--University of South Carolina, 1988
Keywords: Andean Pact; ASEAN; Developing countries -- Economic conditions; Economic Community of West African Studies (ECOWAS).; International economic integration; International economic relations